QUANTUM ATTACKS ON CLASSICAL CRYPTOSYSTEM - Cygan, Weronika; Dajka, Jerzy (No Limits, 2022)
What is quantum cryptography? Can classical banknote security measures be replaced by quantum ones? How to deal with the threats posed by quantum computers? While many publicists are keen on fearmongering with quantum computers as a challenge to data security, we are by no means helpless in the face of this threat.